Lei Geral de Proteção de Dados Pessoais e o agronegócio: uma análise das implicações aos produtores rurais no município de Palmeira das Missões, Rio Grande do Sul, Brasil. - Stefani, Patricia Figueiredo (2023)
The intense use of personal data by public and private companies, based on modern information technologies, has presented new challenges to the right to privacy. It could not be different in the agribusiness sector, which, driven by digital technologies, began to operate based on data. The movement of agricultural data began to raise caution regarding the collection and storage of information by the parties involved in agricultural processes, at which time it began to reflect on the impact that the General Data Protection Law would cause in the agribusiness sector. The present study aimed to analyze the rural producer's perception in relation to the General Data Protection Law (LGPD) in the municipality of Palmeira das Missões/RS. The study is of the qualitative-quantitative type, used as a data collection instrument a manual that was made available online and in person, which was protected with 48 questions and directed to rural producers. From the research carried out, the result was that the legal object protected by the LGPD is personal data and that they are part of the list of Fundamental Rights, entering the concept of privacy listed in article 5, item X of the Federal Constitution. It was found that the level of implementation of the LGPD in rural properties is currently low due to the lack of knowledge of the law and its legal institutions, whose effect promoted reflections on the process of implementing the said law in rural properties, as well as the ownership of data related to these activities. It was evident that the ownership of data generated from agricultural operations belongs to rural landowners, and companies must adopt behaviors that minimize the risk of data leakage in order to promote the economic and technological development of the production chain. Finally, the lack of information for the rural producer on the part of the organizations involved in the process was evidenced and consequently the need to create awareness and information policies for the effective implementation of the LGPD in order to reach the necessary balance between the availability of digital technologies and the legal framework for data use